HUBUNGAN GLUKOSA DARAH SEWAKTU DENGAN INDEKS MASSA TUBUH PADA USIA PRODUKTIF - Andriana, Jumaini; Prihantini, Nur Nunu; Raizza, Fidella Dary (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2018)
Body Mass Index was found as one of many parameters which have been used to determine body proportion. This study aims to determine the relationship of body mass index (BMI) and glucose levels in the productive age because this is an indication that one may experience a wide variety of metabolic diseases due to control blood glucose and abnormal body mass index. The research method was an observational crossectional. The results shows that GDS normal with normal BMI are 26 respondents (81.3%), and found that the most abnormal GDS is also derived from the normal BMI groups with 6 respondents (18.8%). BMI otherwise unrelated to the productive age’s GDS with p-value correlation with age and GDS is p = 0.537 (p > 0.05) while p-value correlation BMI and GDS is p = 0.203 (p > 0.05).